2006
DOI: 10.1042/bj20051957
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Tiam1 and the Arp2/3 complex links activation of Rac to actin polymerization

Abstract: The Rac-specific GEF (guanine-nucleotide exchange factor) Tiam1 (T-lymphoma invasion and metastasis 1) regulates migration, cell-matrix and cell-cell adhesion by modulating the actin cytoskeleton through the GTPase, Rac1. Using yeast two-hybrid screening and biochemical assays, we found that Tiam1 interacts with the p21-Arc [Arp (actin-related protein) complex] subunit of the Arp2/3 complex. Association occurred through the N-terminal pleckstrin homology domain and the adjacent coiled-coil region of Tiam1. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…However, our immunoblot analysis showed that levels of Par3 were unaffected in CGNL1(-) cells, ruling out this possibility. Although Tiam1 has been reported to interact with several proteins, most of these proteins have been identified in fibroblasts/neurons, and not epithelial cell model systems (Mertens et al, 2003;Ten Klooster et al, 2006). Our results provide the first evidence that depletion of a Tiam1-interacting protein results in decreased accumulation of Tiam1 at epithelial junctions, and increased Tiam1 solubility.…”
Section: Regulation Of Rac1supporting
confidence: 57%
“…However, our immunoblot analysis showed that levels of Par3 were unaffected in CGNL1(-) cells, ruling out this possibility. Although Tiam1 has been reported to interact with several proteins, most of these proteins have been identified in fibroblasts/neurons, and not epithelial cell model systems (Mertens et al, 2003;Ten Klooster et al, 2006). Our results provide the first evidence that depletion of a Tiam1-interacting protein results in decreased accumulation of Tiam1 at epithelial junctions, and increased Tiam1 solubility.…”
Section: Regulation Of Rac1supporting
confidence: 57%
“…S1A). As previously reported (27,38), deletion of the entire PHn domain (⌬PH) of Tiam1 resulted in diffuse cytoplasmic staining with greatly reduced actin-rich protrusions ( Fig. 4B and supplemental Fig.…”
Section: Tiam1 Belongs To a Class Of Spectrin-like Ph Domainssequencesupporting
confidence: 54%
“…Tiam1 also associates with activated Rap1 and in conjunction with the Par polarity complex controls chemokineinduced T-cell polarization (Gerard et al 2007). The association of Tiam1 with IRSp53 and p21Arc provides a direct link between Tiam1-mediated Rac activation and Arp2/3 complex-controlled actin polarization, which is required for cytoskeletal dynamics during cell migration and cell polarization ten Klooster et al 2006). In receptor signaling, activated Ras may activate Rac by direct binding to Tiam1 (Lambert et al 2002) or indirectly by activation of phosphoinositide 3-kinase (PI3-kinase) that may recruit and activate Tiam1 and thereby Rac downstream of Ras (Fleming et al 2000;Zondag et al 2000).…”
Section: Introductionmentioning
confidence: 99%